Stolen fruit: The tropical commodities disaster - Robbins, P. (CTA / Zed Books, 2003)
The author, a leading authority on commodity trading, examines the dependence of many developing countries on the tropical commodities they produce and discusses current trading arrangements. He argues that developing countries must achieve a better balance between supply- and demand-side economics if they secure better prices for their products.